Perancangan Sistem Pelayanan Klinik Gigi Berbasis Web dan Mobile dengan Integrasi Sistem Antrian Digital menerapkan Algoritma First Come First Served (FCFS) - Fitria Dwi Handayani Yusuf; Adam Sekti Aji (Universitas Budi Darma, 2025)
Efficient and responsive dental clinic services are essential for improving patient satisfaction and ensuring streamlined healthcare delivery. However, many independent dental clinics still rely on manual procedures for patient registration, scheduling, and queue management, which often lead to long waiting times, unpredictable service flow, and a high risk of administrative errors. These issues negatively impact the overall quality of service and reduce operational effectiveness. This study aims to design and implement a web- and mobile-based dental clinic service system integrated with a digital queuing mechanism to address these challenges. The system was developed using Flutter as the patient-facing mobile interface, Flask as the backend service responsible for managing business processes, and Supabase as the real-time database and user authentication platform. Key features of the system include patient registration and login, service booking, automated scheduling based on reservation time or arrival order, real-time queue monitoring, electronic medical record management, and integrated digital payments to facilitate transactions. Based on functional and performance testing, the system was able to reduce service processing time by up to 80% compared to manual methods, minimize data entry errors, and significantly improve the accuracy of queue management. User feedback also indicated that the system provides a more convenient and informative experience, as patients can easily monitor their queue position through the mobile application. Overall, the proposed system effectively enhances service efficiency, data accuracy, and the quality of dental clinic operations, while also demonstrating strong potential for further development and scalability across larger healthcare facilities